Using vlogs to improve speaking skills for fourth semester students of STKIP PGRI Bangkalan - Maskuroh, Maskuroh; Ulfa, Siti Maria (Universitas PGRI Madiun, 2024)
The rapid development of technology has resulted in many changes, especially in the world of education. The use of vlogs today is one of the impacts caused by technological developments or digital lifestyles. Video blogging (vlog) is the process of making videos with audio visuals instead of using words. This study will examine the use of vlogs in improving the speaking skills of fourth semester students at STKIP PGRI Bangkalan. The research aims to find out how the use of vlogs improves students' speaking skills and wants to know the students' response to the use of vlog media for learning to speak. The research was conducted at STKIP PGRI Bangkalan, and the subjects of this study were third semester students of the English education study program. This research is a qualitative research, and the data collection technique used was interviews. The interviews involved five fourth semester students. The results showed that vlogs make it easier for students to practice speaking skills because before being displayed on the camera screen, students prepare in advance what they will say. Additionally, the use of vlogs is effective for speaking learning. Through vlogs, students can improve their shortcomings in speaking, such as pronunciation, vocabulary, grammar, and lack of confidence.